School choice and social justice - Brighouse, Harry (Oxford University Press, 2000)
The author provides a new theory of justice for education, arguing that justice requires that all children have a real opportunity to become autonomous persons, and that the state use a criterion of educational equality for deploying educational resources. Through systematic presentation of empirical evidence, the author argues that existing schemes do not fare well against the criterion of social justice, yet this need not impugn school choice. Brighouse offers a school choice proposal that could implement social justice and explains why other essential educational reforms can be compatible with choice.